Understanding vitamin B12 - Hüpsch-Marzec, Hanna; Pawlak, Roman; Skaba, Dariusz (Journal of Stomatology, 2019)
Dentists often act as primary care physicians. If they are able to identify symptoms of vitamin B12 deficiency, dentists can identify the problem at the early stage of the pathology. They can make appropriate referrals to specialists who can make a diagnosis and recommend treatment. Effective treatment may be possible at the stage before neurological symptoms occur, preventing irreversible changes to the body. Vitamin B12 (cobalamin) plays an essential role in many metabolic processes, including biosynthesis of nucleic acids. The clinical manifestations of vitamin B12 deficiency are highly polymorphic and depend on many factors. This review presents fundamental information about the structure of vitamin B12, its dietary sources, up-to-date understanding of its role in the human body and the most important consequences of its deficiency, including manifestations within the mucous membrane of the oral cavity. Due to the fact that a large percentage of adults and elderly patients have an undiagnosed vitamin B12 deficiency it is prudent to screen for vitamin B12 status. Methylmalonic acid and/or holotranscobalamin II (holoTCII) have been proposed to be the most sensitive assessment methods. Among high risk groups (e.g. the elderly, vegetarians, people with gastrointestinal health conditions), screening should be recommended at each annual examination.